Experimental and numerical investigations of masonry ‎ beams performance under bending loads (Fracture and Structural Integrity, 2023)
An experimental and numerical study was achieved to investigate the behavior of masonry beams internally reinforced using carbon fiber-reinforced polymer (CFRP) and hybrid steel/CFRP reinforcements. In addition, the use of masonry equivalent material characteristics in the numerical modeling instead of modeling the blocks and mortar was evaluated. Three beams were built using cement bricks and tested in three-point bending with an effective simply supported span of 840 mm. The bricks were designed with a hole that was filled with grout before placing the rebar inside. Material characterization tests were performed to evaluate the mechanical properties of the brick, mortar, and masonry blocks. The beam samples were tested under static loads and the load deformation and failure load were monitored. Finite element methods were built for the beams and validated using the experimental results. The model was used to study more parameters such as the distance between the stirrups and the hybrid reinforcement configuration. Results showed that hybrid reinforcement is the best reinforcement configuration. It can be concluded that the reinforced masonry systems were able to achieve flexural resistance with maximum resistance when using the hybrid reinforcement.
Keywords: Experimental; ANSYS; CFRP; Hybrid reinforcement; Static loading; Masonry beams